Fear and Obedience: Mengungkap Kekerasan Seksual Terhadap Istri melalui Photovoice - Muhammad Reza Firmansyah; Melinda The; Wawan Kurniawan (Universitas Andalas, 2025)
Despite three years of implementing the Law on Sexual Violence Crimes (UU TPKS) in Indonesia, the number of sexual violence cases remains high, leading this study to focus on wives experiencing domestic sexual violence who choose not to pursue legal action. Employing the empowering photovoice method, which allows participants to share their experiences through photos and narratives, this research reveals the types of sexual violence experienced and their reasons for remaining in abusive relationships. The findings reveal four categories of sexual violence: physical/non-physical sexual harassment, sexual torture, and marital rape. Wives choose to stay due to fears concerning their children's future and the belief in the